1998
DOI: 10.1103/physreve.58.3055
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized delayed-feedback control of a coupled map model for open flow

Abstract: A decentralized delayed-feedback control of a coupled map model for open flow is studied theoretically. The decentralized controllers can suppress turbulent behavior in the open flow model. The stability of the control system is analyzed, and then we provide a procedure to design the decentralized controllers from uncertain information of the local map and the coupling strength. The theoretical results are verified by some numerical simulations. ͓S1063-651X͑98͒06209-6͔ PACS number͑s͒: 05.45.ϩb PHYSICAL REVIEW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The spatiotemporal stability of homogeneous solution (2) of system (1) [Konishi et al, 1998[Konishi et al, , 2000b[Konishi et al, , 2001]. …”
Section: An Experimental Suppression Of Spatial Instability 2899mentioning
confidence: 99%
See 2 more Smart Citations
“…The spatiotemporal stability of homogeneous solution (2) of system (1) [Konishi et al, 1998[Konishi et al, , 2000b[Konishi et al, , 2001]. …”
Section: An Experimental Suppression Of Spatial Instability 2899mentioning
confidence: 99%
“…The DFC method has been widely applied to real systems, since it is a practical scheme for experimental situations [Chen & Dong, 1998]. In recent years, an increasing interest has been devoted to the study of spatiotemporal chaos and its control [Astakhov et al, 1995;Hu et al, 1997;Konishi et al, 1998Konishi et al, , 2000a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is confirmed that ʈG(s)ʈ ϱ is greater than 1 and G(s) is stable. The trajectories in the phase plane for sites 5,8,11,13,30, and 50 are shown in Fig. 6.…”
Section: ͑43͒mentioning
confidence: 99%
“…They are classified into several types according to the connection and the boundary conditions. Among them, the one-way open CML is well known as a typical open flow model [1]- [5]. Kaneko discovered a spatial perio-doubling bifurcation in the one-way open CML [2], and it was examined in detail by numerical simulations [3], [4].…”
Section: Introductionmentioning
confidence: 99%